Pharmaceutical occurrence in groundwater and surface waters in forests land‐applied with municipal wastewater. (9th December 2015) - McEachran, Andrew D.; Shea, Damian; Bodnar, Wanda; Nichols, Elizabeth Guthrie
Abstract: The occurrence and fate of pharmaceutical and personal care products in the environment are of increasing public importance because of their ubiquitous nature and documented effects on wildlife, ecosystems, and potentially humans. One potential, yet undefined, source of entry of pharmaceuticals into the environment is via the land application of municipal wastewater onto permitted lands. The objective of the present study is to determine the extent to which pharmaceuticals are mitigated by or exported from managed tree plantations irrigated with municipal wastewater. A specific focus of the present study is the presence of pharmaceutical compounds in groundwater and surface water discharge. The study site is a municipality that land‐applies secondary treated wastewater onto 930 hectares of a 2000‐hectare managed hardwood and pine plantation. A suite of 33 pharmaceuticals and steroid hormones was targeted in the analysis, which consisted of monthly grab sampling of groundwater, surface water, and wastewater, followed by concentration and cleanup via solid phase extraction and separation, detection, and quantification via liquid chromatography coupled with tandem mass spectrometry. More than one‐half of all compounds detected in irrigated wastewater were not present in groundwater and subsequent surface water. However, antibiotics, nonsteroidal anti‐inflammatory drugs, caffeine, and other prescription and over‐the‐counter drugs remained in groundwater and were transported into surface water at concentrations up to 10 ng/L. These results provide important documentation for pharmaceutical fate and transport in forest systems irrigated with municipal wastewater, a previously undocumented source of environmental entry. Environ Toxicol Chem 2016;35:898–905. © 2015 SETAC